Induced degeneration and regeneration in aged muscle reduce tubular aggregates but not muscle function - Felipe Tadeu Galante Rocha de Vasconcelos; Antonio Fernando Ribeiro Júnior; Brandow Willy Souza; Isabela de Aquino Zogbi; Laura Machado Lara Carvalho; Letícia Nogueira Feitosa; Lucas Santos Souza; Nathália Gagliardi Saldys; Merari de Fátima Ramires Ferrari; Mariz Vainzof (Frontiers in Neurology, 2024)
IntroductionTubular aggregates (TA) are skeletal muscle structures that arise from the progressive accumulation of sarcoplasmic reticulum proteins. Cytoplasmic aggregates in muscle fibers have already been observed in mice and humans, mainly during aging and muscle disease processes. However, the effects of muscle regeneration on TA formation have not yet been reported. This study aimed to investigate the relationship between degeneration/regeneration and TA in aged murine models. We investigated the presence and quantity of TA in old males from two murine models with intense muscle degeneration and regeneration.MethodsOne murine lineage was a Dmdmdx model of Duchenne muscular dystrophy (n = 6). In the other model, muscle damage was induced by electroporation in C57BL/6J wild-type mice, and analyzed after 5, 15, and 30 days post-electroporation (dpe; n = 15). Regeneration was evaluated based on the quantity of developmental myosin heavy chain (dMyHC)-positive fibers.ResultsThe frequency of fibers containing TA was higher in aged C57BL/6J (26 ± 8.3%) than in old dystrophic Dmdmdx mice (2.4 ± 2%). Comparing the data from induced degeneration/regeneration in normal mice revealed a reduced proportion of TA-containing fibers after 5 and 30 dpe. Normal aged muscle was able to regenerate and form dMyHC+ fibers, mainly at 5 dpe (0.1 ± 0.1 vs. 16.5 ± 2.6%). However, there was no difference in force or resistance between normal and 30 dpe animals, except for the measurements by the Actimeter device, which showed the worst parameters in the second group.DiscussionOur results suggest that TA also forms in the Dmdmdx muscle but in smaller amounts. The intense degeneration and regeneration of the old dystrophic model resulted in the generation of new muscle fibers with a lower quantity of TA. Data from electroporated wild-type mice support the idea that muscle regeneration leads to a reduction in the amount of TA. We suggest that TA accumulates in muscle fibers throughout physiological aging and that regeneration leads to the formation of new fibers without these structures. In addition, these new fibers do not confer functional benefits to the muscle.